The impact of antidepressant medications on the course of inflammatory bowel diseases - Karol Kasprzak; Agnieszka Dyzma-Kasprzak; Zuzanna Wingralek; Albert Sikorski; Wiktoria Sikorska; Jolanta Wiśniewska; Agnieszka Banaszek; Olga Nowacka (Kazimierz Wielki University, 2024)
Introduction and Objective: Inflammatory bowel diseases (IBD) and anxiety, as well as depressive disorders, can coexist. Depression may affect IBD symptoms and vice versa. The aim of our study is to determine the impact of different classes of antidepressant medications in the treatment of IBD with comorbid depressive episodes, to summarize the most commonly used therapies, and to identify the most effective practices in treating inflammatory diseases with coexisting depressive episodes. Materials and Methods: A review of the available literature was conducted by searching the PubMed and Google Scholar databases using the following keywords: inflammatory bowel diseases, depression, antidepressants, in both English and Polish, up until July 19, 2024. To ensure the high quality of the narrative review, the SANRA scale (a scale for the quality assessment of narrative review articles) was used. Results: Studies indicate that depressive symptoms occur in approximately 25-27.5% of patients with inflammatory bowel diseases (IBD). Treatment of depression in IBD patients often includes the use of antidepressant medications, such as selective serotonin reuptake inhibitors (SSRIs), which not only reduce depression but also exhibit anti-inflammatory effects. SSRIs may also be effective in improving patients' quality of life; however, they may cause side effects such as diarrhea and an increased risk of bleeding. In addition to SSRIs, other antidepressants, such as serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), and atypical antipsychotics, are also used and may have a beneficial impact on the course of the disease. Conclusions: In patients with IBD and comorbid depression, SSRIs are most commonly used, followed by TLPDs, SNRIs, and atypical antipsychotics. Drugs from these groups may have a beneficial effect on depressive symptoms, but also affect the course of IBD. Further clinical studies are needed to establish precise guidelines for the use of these drugs in patients with IBD.